2012
DOI: 10.1111/j.1600-0412.2012.01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental mesenchymal dysplasia and an estimation of the population incidence

Abstract: Placental mesenchymal dysplasia (PMD) is a rare placental malformation of as yet undetermined etiology. We report a single center's experience of this diagnosis and present an estimation of the population incidence. Within our institution, all placentae are examined within a pathology department that provides a dedicated perinatal service. In this study, we evaluated the incidence of PMD over a period of 18 years following the description and recognition of PMD as a pathological diagnosis. During the period 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 10 publications
0
34
0
2
Order By: Relevance
“…Of the 110 cases reviewed, 16 (14.5%) were associated with BWS [2,3,4,5,6,7,8,9,10], 33 (30.0%) had evidence of fetal growth restriction [4,11,12,13,14,15,16,17,18,19,20,21,22,23,24,41,46,48] as in the current case, and 28 (25.5%) ended in intrauterine fetal death [4,6,7,8,12,13,15,16,17,18,25,26,45,47]. There is a female preponderance in cases of PMD; of the infant data reviewed, there were 78 females and 19 males.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 110 cases reviewed, 16 (14.5%) were associated with BWS [2,3,4,5,6,7,8,9,10], 33 (30.0%) had evidence of fetal growth restriction [4,11,12,13,14,15,16,17,18,19,20,21,22,23,24,41,46,48] as in the current case, and 28 (25.5%) ended in intrauterine fetal death [4,6,7,8,12,13,15,16,17,18,25,26,45,47]. There is a female preponderance in cases of PMD; of the infant data reviewed, there were 78 females and 19 males.…”
Section: Resultsmentioning
confidence: 99%
“…Another characteristic feature of PMD is aneurismal and varicose dilation of fetal chorionic vessels. Of the 110 cases reviewed, 48 cases of PMD presented data of dilation of fetal chorionic vessels [2,3,9,11,12,13,14,15,17,18,20,21,22,23,24,26,34,35,36,40,41,44,45,46,47,48]. Figure 6 represents the gestational age when aneurismal and varicose dilation of chorionic vessels were identified in the 48 cases and the current case.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…True incidence is not known but it has been estimated at 0.02% [4]. However, Zeng et al [5] identified only two cases in 95000 deliveries at their institution. They reported the incidence of 0.02 per 1000, which was lower than that reported before by Arizawa and Nakayama [4].…”
Section: Discussionmentioning
confidence: 99%